The Role of Political Economy of Communication in the Formation of Global Strategies - Cereci, Sedat (Atlas Journal, 2024)
In this study, attempts and techniques to manipulate societies and dominate people through high communication technologies are discussed. While Edward S. Herman and Noam Chomsky’s Propaganda Model and Edward L. Bernays’ Consent Engineering theories found their living applications in the period when communication technology was at its highest; It has also been the main means of application for those who want to have power in the world and control people. According to Foucault, while power emerges as an absolute influence on the actions of the subjects rather than over the subjects as an other, in the hypermodern age where technology has reached its highest dimensions, there are high technologies that control and regulate the actions of people. In this context, public relations and propaganda activities carried out through mass media in order to manipulate the masses in order to form and shape public opinion. While more than half of the total population in the world uses the internet and social media, they do not realize how they are managed, controlled and manipulated. The powers that dominate people with high communication technologies decide and direct people in everything from how people will live to what they will do. Evolving with high communication technologies, people and the world are also witnessing the change of economic and political strategies and take their place in the game as the passive leading actor of this change.